Antioxidant activity of Moringa oleifera tissue extracts - Santos, Andréa F. S. (2012)
Moringa oleifera is an important source of antioxidants, tools in nutritional biochemistry that could be beneficial for human health; the leaves and flowers are used by the population with great nutritional importance. This work investigates the antioxidant activity of M. oleifera ethanolic (E1) and saline (E2) extracts from flowers (a), inflorescence rachis (b), seeds (c), leaf tissue (d), leaf rachis (e) and fundamental tissues of stem (f). The radical scavenging capacity (RSC) of extracts was determined using dot-blots on thin layer chromatography stained with a 0.4 mm 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) solution; spectrophotometric assays were recorded (515 nm). Antioxidant components were detected in all E1 and E2 from a, b and d. The best RSC was obtained with E1d; the antioxidants present in E2 reacted very slowly with DPPH. The chromatogram revealed by diphenylborinate-2-ethylamine methanolic solution showed that the ethanolic extract from the flowers, inflorescence rachis, fundamental tissue of stem and leaf tissue contained at least three flavonoids; the saline extract from the flowers and leaf tissue revealed at least two flavonoids. In conclusion, M. oleifera ethanolic and saline extracts contain antioxidants that support the use of the plant tissues as food sources.